2016
DOI: 10.1902/jop.2015.150464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Antibiotic Prophylaxis on Wound Healing After Flapless Implant Surgery: A Pilot Study

Abstract: The local application of antibiotics along with the systemic antibiotics could reduce the inflammatory response in wound healing after implant surgery. The EEO and MHO were equally effective in early wound healing. Compared to the MHO, the EEO has advantages of higher cost efficiency and convenience. Therefore, it is recommended to use the EEO in topical antibiotic prophylaxis for wound healing after flapless implant surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…The signi icant wound healing activity revealed due to their ability for decreasing the response of in lammation at the wound area. The result was come in accordance with [31] they found that local application of antibiotics could reduce the in lammatory response in wound healing. Also this result come in accordance with [32] about the role of Rapamycin on Wound Healing in wound healing as affected all steps of the wound healing process by decreasing the in lammatory cell number, angiogenesis, and myo ibroblast proliferation.…”
Section: Discussionsupporting
confidence: 84%
“…The signi icant wound healing activity revealed due to their ability for decreasing the response of in lammation at the wound area. The result was come in accordance with [31] they found that local application of antibiotics could reduce the in lammatory response in wound healing. Also this result come in accordance with [32] about the role of Rapamycin on Wound Healing in wound healing as affected all steps of the wound healing process by decreasing the in lammatory cell number, angiogenesis, and myo ibroblast proliferation.…”
Section: Discussionsupporting
confidence: 84%
“…Azithromycin seemed to alter some potentially important aspects of inflammation, suggesting azithromycin may have a favorable influence on healing compared with amoxicillin. Moreover, Xu et al 32 recently found the local application of topical antibiotics combined with systemic antibiotic therapy reduced inflammation postoperatively and could enhance early wound healing after flapless implant surgery. A summary of the findings in the literature regarding the use of prophylactic antibiotics for dental implant placement is provided in Table 1.…”
Section: Clinical Methodsmentioning
confidence: 99%
“…Xu et al 32 Pilot Systemic antibiotic (not described) combined with topical application:1) MHO or 2) EEO or systemic antibiotic without topical application The local application of antibiotics along with systemic antibiotics could reduce the inflammatory response in wound healing after flapless implant surgery.…”
Section: Decrease Early Peri-implant Inflammationmentioning
confidence: 99%
“…Xu et al expressed concerns about the difficulty of limited information available to practitioners for stringent control of post-operative complications following implant procedures. 2 Furthermore, current literature demonstrates significant variability among practitioners' antibiotic prescribing patterns, prompting the need to assess how varying interventions affect the overall success of implant operations. 3 Dental implants generally exhibit high initial success rates, but failures occur occasionally.…”
Section: Introductionmentioning
confidence: 99%